Answers

2016-04-10T00:11:44+05:30
Sin^6A+cos^6A
(sin²A)³+(cos²A)³ ............[a^6=(a²)³]
(sin²A+cos²A)³-3sin²Acos²A.........[(a+b)³=a³+b³+3ab]
1³-3sin²Acos²A
1-3sin²Acos²A

!!hence proved!!


 

0
hope it helps
u made some mistakes in the answer.
check the formula.
its absolutely correct
(a+b)^3=a^3+b^3+3ab(a+b) (a+b)^3-3ab(a+b)=a^3+b^3
2016-04-10T10:17:18+05:30
Sin⁶A+cos⁶A = (sin²A)³ + (cos²A)³
                       = ( sin²A+cos²A)³ - 3(sin²A.cos²A)(sin²A+cos²A)
                       = 1 - 3(sin²A.cos²A)(1)
                       = 1 - 3.sin²A.cos²A
0